The Visegrad Group countries: The United Arab Emirates Perspective - Krzymowski Adam (Sciendo, 2021)
This manuscript analyses the role and importance of cooperation between the Visegrad Group (V4) countries and the most globally active member of the Gulf Cooperation Council (GCC), which is the United Arab Emirates. In view of the V4+ concept implemented with partners from the Middle East, Israel or Egypt, the presented analysis is important and meets the lack of this element in the scientific debate. This study is based on empirical research and its findings are the result of not only observation but also 10 years of direct participation of the author in many activities related to the cooperation of the Visegrad Group countries and the UAE, including as ambassador, senior advisor to Dubai Expo 2020, especially responsible for strategies and dynamisation relations between Central and Eastern Europe (except Poland) and the United Arab Emirates. According to the author’s opinion, presented in the conclusion, there is now a huge opportunity to present V4 projects, including as a part of the broader strategy of the Three Seas Initiative (3SI) during World Expo Dubai, which will take place from October 2021 to March 2022, and make this initiative a globally recognizable project. However, coordinating and accelerating joint actions is required.